[PR counsel for Mass Clean indoor air legislation] - Susan Stuntz (Tufts Archival Research Center, 2007)
Memorandum from Dennis Dyer to Susan Stuntz regarding PR support for the Mass. AFL-CIO. Claims that neither the LMC nor the TI can provide the support and that it may be necessary to hire and pay directly, Kate McGrath.